2015
DOI: 10.1515/hmbci-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

The effects of short-term high-intensity interval training vs. moderate-intensity continuous training on plasma levels of nesfatin-1 and inflammatory markers

Abstract: Both the HIIT and MCT groups had similar effects on inflammatory markers and insulin resistance in men who are overweight, but the HIIT seems to have better anorectic effects (as indicated by nesfatin) compared with MCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 37 publications
(59 reference statements)
3
72
0
1
Order By: Relevance
“…Our data are consistent with those studies who's investigated the effects of different mode acute/ chronic exercise training on plasma nesfatin-1 in human and animal subjects [69][70][71][72]. In our study, we observed a lower ghrelin mRNA expression in both saline and Bane-trained liver, not in visceral fat tissue.…”
Section: Figure 8 Plasma Estradiol Level In Different Groupssupporting
confidence: 93%
“…Our data are consistent with those studies who's investigated the effects of different mode acute/ chronic exercise training on plasma nesfatin-1 in human and animal subjects [69][70][71][72]. In our study, we observed a lower ghrelin mRNA expression in both saline and Bane-trained liver, not in visceral fat tissue.…”
Section: Figure 8 Plasma Estradiol Level In Different Groupssupporting
confidence: 93%
“…Interventions were conducted for 10.4 ± 3.1 weeks (range 5-16 weeks), and the mode of exercise was matched for HIIT and MICT interventions in all studies. Cycle ergometer was the most common modality (seven studies (24,25,27,30,32,34,35)), followed by treadmill running (six studies (23,26,28,29,31,33)).…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
“…All data for whole-body fat levels (N = 11 studies) were drawn from studies applying either DXA (seven studies (24,25,28,31,32,34,35)) or BIA (four studies (23,26,30,33)). Six studies reported whole-body lean mass (four studies using DXA (27,28,34,35) and two studies using BIA (26,30)), four studies reported trunk fat values (three studies using DXA (25,27,35) and one using BIA (30)) and one CT study provided visceral fat as a measure (33).…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of training improves physical condition and capacity, fostering an improvement in glucose metabolism and burning fat reserves (Motta et al, 2015;Smith-Ryan et al, 2015). Both the HIIT and moderate-intensity continuous exercise training (MICT) led to similar effects on inflammatory markers (nesfatin-1, interleukin-6, and tumor necrosis factor alpha), and insulin resistance in men who are overweight, but the HIIT seems to have better anorectic effects (as indicated by nesfatin) compared with MICT (Ahmadizad et al, 2015). HIIT significantly increases cardiorespiratory fitness by almost double that of MICT in patients with lifestyle-induced chronic diseases (Weston et al, 2014).…”
Section: Introductionmentioning
confidence: 99%